Breeding, Moulting, and Site Fidelity of Brant (Branta bernicla) on Bathurst and Seymour Islands in the Canadian High Arctic - O'Briain, Michéal; Reed, Austin; Macdonald, Stewart D. (ARCTIC, 1998)
We studied the breeding and moulting ecology of eastern High Arctic brant Branta bernicla hrota on Bathurst and Seymour Islands in the central Canadian High Arctic from 1968 to 1989. In most years, brant arrived in Polar Bear Pass, Bathurst Islnd, during the first few days of June (earliest 28 May 1977), where they fed for several days in small flocks before dispersing to nesting areas. First eggs were usually laid on 13 June and the peak of nest initiation occurred about 16 June. The mean clutch size was 4.5 eggs, and the mean incubation period 23 days. Broods were raised along the shorelines of lakes, ponds, estuaries, and rivers. Goslings were capable of flight by 42-43 days. During the 10 years when the studies were most intensive (1974-77 and 1984-89), there were three years in which brant did not attempt to nest (1974, 1986, 1988); they nested in all other years and were known to produce fledged young in at least four of them. Nesting was not attempted when the mean temperature for the period 1-20 June was below -3 C. On Bathurst Island in 1987, arctic foxes (Alopex lagopus) preyed heavily on brant eggs, and no young were fledged. Nonbreeding adults assembled in small flocks to moult around nerby inland lakes, in river valleys, and at the mouths of estuaries, and concentrated in the latter in cold summers when inland sites had heavier ice cover. The flightless period began about 6 July and lasted 20-22 days. The recapture or resighting of brant marked on Bathurst Island showed that many adults returned in subsequent years to the same breeding territories, and in nonbreeding years they moulted nearby. A smaller proportion of the brant that had been marked as goslings and yearlings also returned to the island. In comparison with most other stocks of North American brant, those we studied bred at high latitude. That choice of breeding site subjected them to periodic breeding failures caused by cold springs and to a reduced availability of plant biomass, but it offered the advantage of reduced spring snow ...